2016
DOI: 10.3892/or.2016.5205
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-suppressive role of HACE1 in hepatocellular carcinoma and its clinical significance

Abstract: An increasing body of evidence suggests that downregulation or deletion of HECT domain and ankyrin repeat containing E3 ubiquitin protein ligase 1 (HACE1) gene plays an important role in the occurrence, invasion and metastasis process in many human malignancies and is closely related to prognosis. However, sparse evidence exists concerning the precise function and clinical significance of HACE1 in hepatocellular carcinoma (HCC). In the present study, we investigated the expression pattern of HACE1 in HCC tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 24 publications
(25 reference statements)
1
26
0
Order By: Relevance
“…HACE1 was found low expressed in previous studies about breast cancer , colorectal cancer , liver cancer and leukemia . In this study, we also spotted a significant down‐regulation of HACE1 in gastric cancer tissues compared with their adjacent normal tissues.…”
Section: Discussionmentioning
confidence: 73%
“…HACE1 was found low expressed in previous studies about breast cancer , colorectal cancer , liver cancer and leukemia . In this study, we also spotted a significant down‐regulation of HACE1 in gastric cancer tissues compared with their adjacent normal tissues.…”
Section: Discussionmentioning
confidence: 73%
“…A previous study reported that HACE1 has a tumour-suppressive role in hepatocellular carcinoma (5). To evaluate whether CRISPR-Cas-induced upregulation of HACE1 resulted in physiologically relevant effects, the proliferation of Hep3B and HepG2 cells was detected by MTT assays at 24 and 48 h post transfection.…”
Section: Demethylation Of Hace1 Inhibits Human Liver Cancer Cell Prolmentioning
confidence: 99%
“…The majority of liver cancer cases are diagnosed at an advanced or unresectable stage; therefore, novel therapeutic strategies and therapeutic targets are required. Current studies mainly focus on the pathogenic genes and molecular mechanisms involved in liver cancer (5,6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The HACE1 is expressed in brain, heart, lung, kidney, testis, and ovary [13,15]. Several studies have implicated that HACE1 is a candidate chromosome 6q21 tumor suppressor gene involved in multiple cancers [1618]. Recently, it has been reported that HACE1 gene may play a role in neurodegeneration [19] and autophagy pathway [20]; while HACE1 mutations are involved in an autosomal recessive neurodevelopmental disorder [21], and glutamine addiction [22].…”
Section: Introductionmentioning
confidence: 99%